2019
DOI: 10.9734/sajrm/2019/v3i130077
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Silver Nanoparticles Produced by Plant Extracts and Its Antimicrobial Activity

Abstract: Solanum tubersum is the fourth most challenging plant in Egypt, affected by several fungi, viral and bacterial diseases. Bacterial and fungal isolates (Brown rot disease (Ralstonia solaniserum), soft root disease (Pectobacterium carotovora) and dry rot disease (Fusarium oxisporum) were collected. The green extracts of silver nanoparticles were prepared by means of aqueous extracts of three wild plants, Physalis peruviana (leaves, red and green fruits) (N1, N2 and N3), Solanum nigrum (fruit) (N4) and Moringa ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…carotovora isolates on different potato cultivars. This finding aligns with a previous study where potato parts inoculated with different bacterial isolates exhibited rapid rot and discoloration after 24 h [ 52 ]. A previous research has also confirmed the variation in sensitivity to bacterial soft rot among potato cultivars [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…carotovora isolates on different potato cultivars. This finding aligns with a previous study where potato parts inoculated with different bacterial isolates exhibited rapid rot and discoloration after 24 h [ 52 ]. A previous research has also confirmed the variation in sensitivity to bacterial soft rot among potato cultivars [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the scientist attempts recorded the increasing of secondary metabolites in plants, the content of vanilla plant Vanilla planifolia increased when nano-silver was added to the MS medium, which was nourished with total phenols and glycosidic compounds due to increased production of ROS (Reactive oxygen species) at concentrations of (25 and 50) mg. L‾¹ (Santoscoy , et al 2017). In a study by ( Javed 2017) when growing the sugar leaf plant Stevia rebaudiana outside the living body to check the impact of different concentrations of nano-zinc oxide (0, 0.1, 1.0, 10, 100, and 1000 mg.L‾¹) in the absence of traditional growth regulators on the production of Secondary compounds, as the results showed superiority to the treatment of 1 mg. L‾¹ of nano-copper oxide increased the production of flavonoids and total phenols, while all studied indicators decreased with increasing concentration of nano-copper oxide ( Samy et al 2019) also indicated their success in using silver nanomaterial produced from the herb extract as an alternative to fungicides to control some bacterial and fungal infections affecting potatoes. Silver nanoparticles can act as a catalyst to produce more copies of the genes of the steviol glycoside biosynthesis pathway, thus increasing the production of this compound Between (Ramezani et.…”
Section: Introductionmentioning
confidence: 82%
“…Among the scientist attempts recorded the increasing of secondary metabolites in plants, the content of vanilla plant Vanilla planifolia increased when nano-silver was added to the MS medium, which was nourished with total phenols and glycosidic compounds due to increased production of ROS (Reactive oxygen species) at concentrations of (25 and 50) mg. L‾¹ (Santoscoy , et al 2017). In a study by ( Javed 2017) when growing the sugar leaf plant Stevia rebaudiana outside the living body to check the impact of different concentrations of nano-zinc oxide (0, 0.1, 1.0, 10, 100, and 1000 mg.L‾¹) in the absence of traditional growth regulators on the production of Secondary compounds, as the results showed superiority to the treatment of 1 mg. L‾¹ of nano-copper oxide increased the production of flavonoids and total phenols, while all studied indicators decreased with increasing concentration of nano-copper oxide ( Samy et al 2019) also indicated their success in using silver nanomaterial produced from the herb extract as an alternative to fungicides to control some bacterial and fungal infections affecting potatoes. Silver nanoparticles can act as a catalyst to produce more copies of the genes of the steviol glycoside biosynthesis pathway, thus increasing the production of this compound Between (Ramezani et.…”
Section: Introductionmentioning
confidence: 82%